Synthesis of Benzo[c]acridine Derivatives: Reaction of N-Arylidenenaphthalen- 1-amine with 5,5-Dimethyl-1,3-cyclohexadione - B. Kasawar, Gajanan; B. Shejul, Pravin; H. Kadam, Nitin; V. Vyavahare, Amol; Panpaliya, Prashant (Asian Journal of Chemistry, 2010)
Synthesis of 10,10-dimethyl-7-aryl-7,9,10,11-tetrahydro- 9H-benzo[c]acridin-8-one derivatives was accomplished in high yields via the reaction of N-arylidenenaphthalen-1-amine with 5,5-dimethyl-1,3-cyclohexadione in aqueous medium catalyzed by triethylbenzyl ammonium chloride. The structures were established from spectroscopic data and melting points.